Encarecimiento de la vivienda y exclusión por el uso de densidades en la zonificación - Kunz Bolaños, Ignacio; Morales Maldonado, Gabriela (El Colegio de México A.C., 2023)
This paper reveals how the use of density as a building parameter in Mexican urban regulation, which aims to manage the intensity of development, has a land prices’ increase effect, higher as the houses get smaller and decrease in quality. This means that low-cost housing production must deal with land costs relatively higher, increasing significantly the huge structural-origin disadvantage that poor families face to get access to housing.